2002
DOI: 10.1088/0953-8984/14/6/103
|View full text |Cite
|
Sign up to set email alerts
|

First principles calculations of niobium substitution in strontium titanate

Abstract: We have studied the effects of Nb incorporation in strontium titanate using DFT plane-wave pseudopotential calculations. Substitution of the impurity on a Ti site in the bulk crystal causes outward relaxations of the neighbouring Ti ions but does not affect the oxygen ions. A conduction band state localized on the Ti ions becomes occupied confirming the donor behaviour of the defect. The formation energy of the impurity is studied under different oxidation conditions. We have also studied the incorporation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 14 publications
2
15
0
Order By: Relevance
“…The optimized lattice constants of the HAp crystal were given in Table 1, together with the results of some other computational and experimental studies. 23,[49][50][51] The deviations are less than 0.05 A for a, b and c, compared to the measurement, and our calculations agree well with other computations. 23,50,51 Generally, the hydroxyl and phosphate groups retain their orientations as in the measurement.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The optimized lattice constants of the HAp crystal were given in Table 1, together with the results of some other computational and experimental studies. 23,[49][50][51] The deviations are less than 0.05 A for a, b and c, compared to the measurement, and our calculations agree well with other computations. 23,50,51 Generally, the hydroxyl and phosphate groups retain their orientations as in the measurement.…”
Section: Resultssupporting
confidence: 86%
“…23,[49][50][51] The deviations are less than 0.05 A for a, b and c, compared to the measurement, and our calculations agree well with other computations. 23,50,51 Generally, the hydroxyl and phosphate groups retain their orientations as in the measurement. The O-H and P-O bond lengths are 0.978 A and 1.535 A, which match well with the measurement (0.971 A and 1.540 A), respectively.…”
Section: Resultssupporting
confidence: 86%
“…In order to maximize TE performance, we showed that the 2-DEG has to be achieved in doped semiconducting nanostructures rather than those with metallic character. [31] Few first-principles studies have investigated the electronic properties of Nb-doped SrTiO 3 [32][33][34] [61]. At this stage, a complete understanding of the transport properties and moreover of the band structure engineering in oxide materials is still missing.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. 18, the structure relaxation due to the Nb dopant and formation energies have been discussed, while Refs. 19 and 20 deal with the effective mass and conductivity.…”
Section: Introductionmentioning
confidence: 99%